Pomegranate seed powder as a functional component of gluten‐free bread (Physical, sensorial and antioxidant evaluation). (2nd April 2018) - Bourekoua, Hayat; Różyło, Renata; Gawlik‐Dziki, Urszula; Benatallah, Leila; Zidoune, Mohammed Nasreddine; Dziki, Dariusz
Summary: The purpose of this study was to evaluate the effect of the addition of pomegranate seed powder (PSP) on physical, sensorial and antioxidant properties of gluten‐free bread. The PSP was incorporated at different levels (2.5%, 5.0%, 7.5% and 10%) into formula of gluten‐free bread. Control gluten‐free bread made without any addition of PSP was used for comparison. The results showed that the specific volume and springiness of gluten‐free breads increased, whereas hardness and chewiness decreased significantly with increasing PSP addition. The addition of PSP into gluten‐free bread decreased the lightness and yellowness of crumb and crust colour, while redness increased. Total phenolics content (TPC) increased from 46% to 181% with PSP addition (2.5%–10%). Moreover, antioxidant activity was significantly higher for bread with PSP. For bread with the highest percentage of PSP, the highest antioxidant activity was obtained. For sensorial and antioxidant activity, the optimum level of PSP addition was found to be 7.5%. Abstract : Different levels of pomegranate seed powder were used to improve the quality of gluten‐free bread. The PSP addition significantly increased the volume and gave a better texture, as well as better antioxidant properties compared to gluten free bread without the addition of PSP.